Urinary tract infection among pregnant Jordanian women: role of hygiene and sexual practices - Reem Hatamleh; Abeer Al-Trad; Sawsan Abuhammad; Mohammed Aljabari; Rachel Joseph (BMC, 2024)
Abstract Purpose The purpose of this study was to examine the association between hygiene and sexual practices and the incidence of urinary tract infection (UTI) among Jordanian pregnant women. Methods The cross-sectional data were collected using self- administered survey from October 2018 to January 2019 in central Jordan. A total of 200 pregnant women completed the survey. All of them were married and aged between 18 and 45 years (M = 27.45; SD = 6.06). The measures used were demographics, social, hygiene and sexual practices. Results A significant association was found between the incidence of UTI and the educational level of husbands (p = 0.05), history of UTI in previous pregnancies (p = 0.02) and being in the second trimester of pregnancy (p = 0.02). Their sexual and hygiene practices also were significantly associated with the incidence of UTI. Conclusion History of UTI in previous pregnancies, hygiene and sexual practices are associated with increased incidence of UTI among Jordanian pregnant women. Appropriate strategies and techniques to promote health and preventive behaviors for pregnant women with UTI should be provided to improve the quality of life among pregnant women and reduces economic burdens on health care system.